Thymoquinone Attenuates Cardiomyopathy in Streptozotocin-Treated Diabetic Rats. (30th October 2018) - Atta, Mustafa S.; El-Far, Ali H.; Farrag, Foad A.; Abdel-Daim, Mohamed M.; Al Jaouni, Soad K.; Mousa, Shaker A.
Abstract : Diabetic cardiomyopathy is a diabetic complication due to oxidative stress injuries. This study examined the protecting influence of thymoquinone (TQ) on diabetes-caused cardiac complications. The intracellular means by which TQ works against diabetes-caused cardiac myopathy in rats is not completely understood. In this study, Wistar male rats (n = 60 ) were assigned into four groups: control, diabetic (diabetes induced by IP infusion of streptozotocin, 65 mg/kg), diabetic + TQ (diabetic rats given TQ (50 mg/kg) administered once per day by stomach gavage), and TQ (50 mg/kg) for 12 weeks. TQ supplementation appreciably recovered the cardiac parameters alongside significant declines in plasma nitric oxide concentrations and total superoxide dismutase (T.SOD) activities. Importantly, TQ downgraded expression of cardiac-inducible nitric oxide synthase in addition to significantly upregulating vascular endothelial growth factor and erythropoietin genes and nuclear factor-erythroid-2-related factor 2 (Nrf2) protein. TQ normalized plasma triacylglycerol and low-density lipoprotein-cholesterol and significantly improved the high-density lipoprotein-cholesterol levels. Additionally, TQ administration improved the antioxidant ability of cardiac tissue via significantly increased cardiac T.SOD and decreased cardiac malondialdehyde levels. Oral supplementation with TQ prevented diabetic-induced cardiomyopathy via its inhibitory effect on the E-selectin level, C-reactive protein, and interleukin-6. The TQ protecting effect on the heart tissue was shown by normalization of the plasma cardiac markers troponin I and creatine kinase. This experiment shows the aptitude of TQ to protect cardiac muscles against diabetic oxidative stress, mainly through upregulation of Nrf2, which defeated oxidative damage by improvement of the antioxidant power of cardiac muscle that consequently protected the cardiac muscles and alleviated the inflammatory process.